A protocol for developing, disseminating, and implementing a core outcome set for endometriosis - Hirsch, M; Duffy, J; Barker, C; Hummelshoj, L; Johnson, N; Mol, B; Khan, K; Farquhar, C (BMJ Publishing Group, 2016)
Introduction Endometriosis is a common gynecological disease characterized by pain and subfertility. Randomized controlled trials evaluating treatments for endometriosis have reported many different outcomes and outcome measures. This variation restricts effective data synthesis limiting the usefulness of research to inform clinical practice. To address these methodological concerns, we aim to develop, disseminate, and implement a core outcome set for endometriosis engaging with key stakeholders, including healthcare professionals, researchers, and women with endometriosis. Methods and analysis An international steering group has been established, including healthcare professionals, researchers, and patient representatives. Potential outcomes identified from a systematic review of the literature will be entered into a modified Delphi method. Key stakeholders will be invited to participate including healthcare professionals, researchers, and women with endometriosis. Participants will be invited to score individual outcomes on a nine point Likert scale anchored between one (not important) and nine (critical). Repeated reflection and rescoring should promote whole and individual stakeholder group converge towards consensus, ‘core’, outcomes. High quality outcome measures will be associated with core outcomes. Ethics and dissemination The implementation of a core outcome set for endometriosis within future clinical trials, systematic reviews, and clinical guidelines will enhance the availability of comparable data to facilitate evidence-based patient care. This study was prospectively registered with Core Outcome Measures in Effectiveness Trials Initiative; number: 691.